Intellectual capital disclosure trends: some Malaysian evidence - Ahmed Haji, Abdifatah; Mohd Ghazali, Nazli Anum (Emerald Group Publishing Limited, 2012)

(untitled)
Purpose – The purpose of this paper is to examine the trend of intellectual capital disclosures (ICD) over a three-year period (2008-2010), when the Malaysian business environment was characterized by a number of major events such as the recent 2008/2009 global financial crisis and corporate governance restructuring.